The Influence of International Trade on Economic Growth - Renny S.Simamora; Dina Auliannia; Khairani Matondang; Revita Yuni (Outline Publisher, 2026)
International trade is trade carried out by residents of a country with residents of other countries on the basis of a mutual agreement. One of the things that determines a country's economic growth is international trade which includes export-import activities. One advantage of international trade is that it allows a country to specialize in producing goods and services at low prices. This study aims to determine the effect of international trade on Indonesia's economic growth. The research method used to solve this problem is a quantitative method using multiple regression analysis and the classic assumption test from secondary data sourced from North Sumatra Economic Data (2001-2020). The results of this study are 1. Partially, imports have a significant positive effect on growth. Economics with the acquisition of a Prob. value of 0.0002 < apha 0.05 so that ha is fulfilled or ho is rejected and for the positive direction it is proven by the Coeffcient which is negative (1.216780). 2. Partially, exports have a negative but not significant effect on economic growth due to the acquisition of a Prob.0.2268> alpha 0.05 value so that ho is fulfilled or ha is rejected and for a negative direction it is proven by a negative Coefficient. (-0.448407) 3. Simultaneously Export and Import have a significant effect on Economic Growth with the acquisition of a Prob (F-Statistic) value of 0.00000 <0.05 meaning that the two variables significantly influence Economic Growth so that ha is fulfilled or ho is rejected 4. The Adjusted R-Square is 0.89, which means that much the two independent variables affect the dependent variable, namely GRDP, which means that there are still other models that affect the dependent variable.